Characterization and Encapsulation of Natural Antioxidants: Interaction, Protection and Delivery - Liang, Li; Cheng, Hao (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on the prediction of antioxidant peptides and the improvement of the aqueous solubility, chemical stability, bioactivity, and release properties of natural antioxidants through enzymatic glycosylation and encapsulation technology. The rational design and construction of delivery systems are effective for the application of antioxidants in the industry. Special attention in this book is given to inorganic nanoparticles, biopolymer-based particulate systems, prediction in antioxidant activity of peptides, evaluation of encapsulation and delivery performance, and application in commercial products.